Practical Implications of Metacognitively Oriented Psychotherapy in Psychosis: Findings From a Pilot Study. Issue 9 (September 2016) - de Jong, Steven; van Donkersgoed, Rozanne J.M.; Aleman, André; van der Gaag, Mark; Wunderink, Lex; Arends, Johan; Lysaker, Paul H.; Pijnenborg, Marieke
Abstract : Abstract: In preparation for a multicenter randomized controlled trial, a pilot study was conducted investigating the feasibility and acceptance of a shortened version (12 vs. 40 sessions) of an individual metacognitive psychotherapy (Metacognitive Reflection and Insight Therapy [MERIT]). Twelve participants with a diagnosis of schizophrenia were offered 12 sessions of MERIT. Effect sizes were calculated for changes from baseline to treatment end for metacognitive capacity measured by the Metacognition Assessment Scale—Abbreviated. Nine of twelve patients finished treatment. However, nonsignificant moderate to large effect sizes were obtained on the primary outcome measure. This study is among the first to suggest that patients with schizophrenia will accept metacognitive therapy and evidence improvements in metacognitive capacity. Despite limitations typical to a pilot study, including a small sample size and lack of a control group, sufficient evidence of efficacy was obtained to warrant further investigation.